Rancang Bangun Sistem Pakar Diagnosa Penyakit Tanaman Pisang Canvendish Dengan Metode Forward Chaining - Kevin Kurniawansyah; Noneng Marthiawati. H; Reni Aryani (STMIK Sinar Nusantara, 2023)
Bananas are part of the horticultural commodity group of fruits which are widely consumed because of their delicious taste and high nutritional content. One of the problems that exist when cultivating canvendish banana plants is the existence of disease disorders that occur in these plants. To prevent this from happening, knowledge about the diseases experienced by these plants is based on the symptoms experienced. Sources of knowledge about the disease and its symptoms can be obtained from an expert. However, the difficulty of consulting with experts in the field of canvendish bananas can be overcome with the help of an expert system to diagnose diseases of canvendish bananas using the Forward Chaining method. The purpose of this research is to help banana farmers or ordinary people to be able to carry out prevention and treatment when bananas are attacked by diseases or pests and overcome existing problems regarding canvendish bananas.